2014
DOI: 10.2337/dc14-0154
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome, Prediabetes, and Brain Abnormalities on MRI in Patients With Manifest Arterial Disease: The SMART-MR Study

Abstract: OBJECTIVEMetabolic syndrome (MetS) is a cluster of cardiovascular risk factors leading to atherosclerosis and diabetes. Diabetes is associated with both structural and functional abnormalities of the brain. MetS, even before diabetes is diagnosed, may also predispose to cerebral changes, probably through shared mechanisms. We examined the association of MetS with cerebral changes in patients with manifest arterial disease. RESEARCH DESIGN AND METHODSCross-sectional data on MetS and brain MRI were available in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
53
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 40 publications
5
53
0
1
Order By: Relevance
“…[22] Only 1 previous study found smaller brain volumes in prediabetic patients using the automated segmentation method. [23] Our results provide the information for brain pathophysiology at the diabetes transition phase. We also found changes in 2 regions that have seldom been studied in previous diabetes research: the PCC and the insula.…”
Section: Discussionmentioning
confidence: 88%
“…[22] Only 1 previous study found smaller brain volumes in prediabetic patients using the automated segmentation method. [23] Our results provide the information for brain pathophysiology at the diabetes transition phase. We also found changes in 2 regions that have seldom been studied in previous diabetes research: the PCC and the insula.…”
Section: Discussionmentioning
confidence: 88%
“…26,[61][62][63][64] Although diabetes is a risk factor for athero sclerosis and incident brain infarcts, most studies found no association or only a weak association between diabetes and WMHs. [65][66][67][68] The combination of arteriolo sclerosis and hyaline wall thickening of the long penetrating arterioles on the one hand and impaired autoregulation on the other could result in hypoxia and ischaemia of the white matter. Impaired blood-brain barrier permeability as a result of ischaemia might lead to leakage of macromolecules, followed by astrocyte activation.…”
Section: Pathophysiology Of Wmhsmentioning
confidence: 99%
“…Однако следует помнить, что висцеральная жировая ткань является метаболически активной в сравнении с подкожной жировой тканью и оказы-вает сильное влияние на продукцию адипокинов и развитие ИР [4,8], поэтому именно ВО ассоцииру-ется со структурными изменениями в ГМ [9] и ухуд-шением КФ [5].…”
Section: Discussionunclassified